Biotelemetry and Radiotracking of Wild Birds: Portable Device Using Solar Cells Power Supply. (1977) - Aucouturier, J. L.; Chaillou, A.; Nicolas, G.; Canivenc, R.; Govaerts, R.; Mertens, R.; Lauwers, F.; Van Overstraeten, R. J.; Marques, M.
Abstract : A thick film hybrid transmitter for the radio tracking of wild animals is described. Weight considerations are of prime importance for such transmitters and the system discussed uses thick film hybrid technology, together with a solar cell power supply charging Cd–Ni batteries. To reduce power consumption a pulsed system is used; the transmitter operating frequency is in the 72 MHz band.